Local Government and Educational Leadership: A SWOT Approach to Sub-District Educational Management in Manado City - Kalesaran, Renaldy J.; Sumual, Shelty D. (JR Education, 2025)
This study applies a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to examine educational management at the sub-district (kecamatan) level in Manado City, Indonesia. Drawing on qualitative and secondary data—including local governance performance reviews, regional public service effectiveness studies, and analyses of educational financing—this paper identifies internal and external factors shaping sub-district educational leadership. Strengths include clear governance mandates and established community collaboration norms; weaknesses involve limited budgetary autonomy, infrastructure gaps, and uneven leadership capacity; opportunities stem from national reform initiatives and participatory budgeting; threats arise from fiscal constraints and political volatility. Based on these findings, the paper recommends targeted capacity-building, enhanced budget flexibility, and formalized stakeholder engagement to improve sub-district educational outcomes.